1997
DOI: 10.1093/oxfordjournals.rpd.a031889
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Concentrations of the Equilibrium-Equivalent Decay Products of 222Rn in the Netherlands and the Effect of Meteorological Variables

Abstract: Airborne radioactivity monitors put up in a network as a warning system in case of nuclear accidents were used to gain insight in the temporal variations of 222Rn and its decay products. Average equilibrium equivalent decay product concentrations (EEDCs) over a period of five years for stations a,cross the country range from I to 3 Bq.m ". Hourly averaged concentrations show a diurnal variation at all stations. The amplitude of this variation is maximal in summer and minimal or nonexistent in winter. Superimpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
2
11
0
Order By: Relevance
“…Their experience contradicts our results, but the buildings in their case were air conditioned which may have significant effect not only on air temperature, but also on relative humidity and concentration of aerosol particles. Blaauboer and Smetsers (1997) found positive correlation between EEC Rn and absolute humidity (measured in g m −3 units) outdoors and found that EEC Rn can be approximated by the function EEC Rn = Constant + 0.007 × (humidity) 2 .…”
Section: Resultsmentioning
confidence: 94%
“…Their experience contradicts our results, but the buildings in their case were air conditioned which may have significant effect not only on air temperature, but also on relative humidity and concentration of aerosol particles. Blaauboer and Smetsers (1997) found positive correlation between EEC Rn and absolute humidity (measured in g m −3 units) outdoors and found that EEC Rn can be approximated by the function EEC Rn = Constant + 0.007 × (humidity) 2 .…”
Section: Resultsmentioning
confidence: 94%
“…There are also other possible sources of 210 Pb like traffic or industrial activities. Simultaneous study of 222 Rn and 210 Pb thus enables to evaluate possible sources of lead from other than natural sources (Fujinami and Esaka, 1987;G€ aggeler et al, 1995;H} otzl and Winkler, 1996;Blaauboer and Smetsers, 1997;Baskaran and Shaw, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the reason that the aerosol particles which carry with them the radon daughters have been known to be hygroscopic in nature. Also, humidity avoids the back radiations from the soil and opposes the formation of inversion layer near the ground [11].…”
Section: Resultsmentioning
confidence: 99%